Significant Output Power Enhancement in Symmetric Dual‐Mode Magneto‐Mechano‐Electric Coupled Resonators. Issue 44 (23rd September 2022) - Yu, Zhonghui; Qiu, Hao; Chu, Zhaoqiang; Sun, Zechen; Pourhosseini Asl, Mohammad Javad; Li, Faxin; Dong, Shuxiang
Abstract: The microenergy harvesting based on magneto‐mechano‐electric (MME) coupling is an emerging technology for powering wireless Internet of Things (IoT) devices because it is capable of simultaneously harvesting magnetic field energy and mechanical energy. However, further improvement in output power of conventional cantilever‐structured MME energy harvesters has met with considerable difficulties due to the inherent, high mechanical energy loss in single‐mode operation. To solve the predicament, here, this work presents a symmetric, mechanical coupled dual‐mode MME energy harvester for restricting clamp loss and then enhancing MME coupling and output power. Under a weak AC magnetic field ( H ac = 4 Oe) at 60 Hz, the MME energy harvester operating in symmetric dual‐mode can generate a peak‐peak output power of 72 mWpp (root‐mean‐square value: 9 mWRMS ), a 437% enhancement over a conventional single‐mode MME energy harvester, which can even drive 160 light emitting diodes (LEDs) lighting directly. A realistic application furtherly shows that the symmetric dual‐mode MME energy harvester can successfully scavenge the magnetic field energy around a household appliance, and the generated electric power can directly drive a wireless IoT system in real time. The proposed concept of symmetric dual‐mode in this work can open new avenues for future vibration‐based energy harvesters design. Abstract : This work presents a symmetric, mechanical coupled dual‐mode magneto‐mechano‐electric energy harvester (MME‐EH) for enhancing MME coupling and output power. Under a weak AC magnetic field of 4 Oe at 60 Hz, the MME‐EH can generate a peak–peak output power of 72 mW, a 437% enhancement over conventional single‐mode MME‐EHs. An equivalent mechanical model is mathematically built to reveal the underlying mechanism.